Thought Reform and the Unreformable: Reeducation Centers and the Rhetoric of Opposition in the Early People's Republic of China. Issue 4 (15th October 2013) - Smith, Aminda M.
Abstract : This essay explores records from Beijing's efforts to intern and reform the city's "lumpenproletariat" after 1949. Connecting these reports to central government directives about national thought reform policy, I show that reeducators and their superiors discoursed in detail about the existence of resisters, who opposed and defied the government, but whom reformatory staff explicitly labeled as non-enemies. The case of Beijing reformatories suggests that anti-state, but non-counterrevolutionary resistance was an important symbolic and rhetorical category, central to the Chinese Communist Party's articulation of its own purpose. In the context of reeducation, opposition to the party-state constituted evidence of a founding "truth": feudal, imperialist, and capitalist oppression had so damaged the Chinese nation that only a radical and revolutionary transformation could save it. Over the course of the 1950s, reading and analyzing resistance in this way led policy makers to redefine "The People" as well as the social place of individuals accused of activities like prostitution, begging, and petty crime.